Feasibility and Clinical Value of CT-Guided 125I Brachytherapy for Pain Palliation in Patients With Breast Cancer and Bone Metastases After External Beam Radiotherapy Failure - He, Jian; Mai, Qicong; Yang, Fangfang; Zhuang, Wenhang; Gou, Qing; Zhou, Zejian; Xu, Rongde; Chen, Xiaoming; Mo, Zhiqiang (Frontiers in Oncology, 2021)
Objectives: To evaluate the feasibility and clinical value of CT-guided iodine 125 (125I) brachytherapy for pain palliation in patients with breast cancer and bone metastases after external beam radiotherapy failure. Methods: From January 2014 to July 2016, 90 patients who had received standard therapies for bone metastases, but still suffered moderate to severe pain, were retrospectively studied. 42 patients had treated with 125I brachytherapy and bisphosphonates (Group A), and 48 patients received bisphosphonates alone (Group B). Results: In Group A, 45 125I brachytherapy procedures were performed in 42 patients with 69 bone metastases; the primary success rate of 125I seed implantation was 92.9%, without sever complications. Regarding pain progression of two groups, Group A exhibited significant relief in “worst pain”, “least pain”, “pain on average” and “pain right now” 3 days post-treatment, and could achieve 12 weeks remission for “worst pain”, “least pain”, “pain on average” and “pain right now”. The morphine-equivalent 24-hour analgesic dose at 3 days, 4 weeks, 8 weeks and 12 weeks were 91±27 mg, 53±13 mg, 31±17 mg and 34±12 mg for Group A, and 129±21 mg, 61±16 mg, 53±15 mg and 105±23 mg for Group B. Group A experienced a lower incidence of analgesic-related adverse events and better quality of life than Group B. Conclusion: CT-guided 125I brachytherapy is a feasible and effective treatment for palliation of pain caused by bone metastases from breast cancer after external beam radiotherapy failure.